Possibility of Implementation of the Complete Cycle of Synthesizing Bulk Polycrystalline Titanium Nitride with Submicron Composition by Plasmodynamic Methods; Russian Physics Journal; Vol. 55, iss. 9 - Evdokimov A. A. Andrey Anatolievich; Sivkov A. A. Aleksander Anatolyevich; Gerasimov D. Yu. Dmitry Yurievich; Saigash A. S. Anastasiya Sergeevna; Khasanov A. O. Aleksey Olegovich (2013, 2013)
Title screen